Managing fluency and disruptive behaviours in children who stutter: An integrated behavioural and stuttering treatment program - Druker, Kerianne Chloe (Curtin University, 2020)
This research investigated specific factors that contribute to a young child’s persistence or recovery from their lifelong disability of stuttering. It determined unique factors in the child’s temperament and developed and evaluated a new clinical treatment to meet these individual needs. The research combined fluency treatment with a behavioural self-regulation program which supported the parents to be positive change agents for their child and ensured durability of fluency for their child’s future development and success.